A Time‐Resolved FRET Cell‐Based Binding Assay for the Apelin Receptor. (20th April 2017) - Valencia, Christel; Dujet, Céline; Margathe, Jean‐François; Iturrioz, Xavier; Roux, Thomas; Trinquet, Eric; Villa, Pascal; Hibert, Marcel; Dupuis, Elodie; Llorens‐Cortes, Catherine; Bonnet, Dominique
Abstract: Analogues of apelin‐13 carrying diverse spacers and an ad hoc DY647‐derived fluorophore were designed and synthesized by chemoselective acylation of α‐hydrazinopeptides. The resulting probes retain very high affinity and efficacy for both the wild‐type and SNAP‐tagged apelin receptor (ApelinR). They give a time‐resolved FRET (TR‐FRET) signal with rare‐earth lanthanides used as donor fluorophores grafted onto the SNAP‐tagged receptor. This specific signal allowed the validation of a binding assay with a high signal‐to‐noise ratio. In such an assay, the most potent sub‐nanomolar fluorescent probe was found to be competitively displaced by the endogenous apelin peptides with binding constants similar to those obtained in a classical radioligand assay. We have thus validated the first TR‐FRET cell‐based binding assay for ApelinR with potential high‐throughput screening applications. Abstract : The search is on ! There is still a need for the rapid discovery of apelin receptor ligands for use as pharmacological probes and precursors of drug candidates. As an alternative to radioligand binding assays, we report herein an unprecedented, efficient, robust, and safe time‐resolved binding assay to investigate ligand–apelin receptor interactions at the cell surface with potential application for high‐throughput screening.